Anti-Markovnikov Hydroazidation of Activated Olefins via Organic Photoredox Catalysis - Onuska, Nicholas P. R.; Schutzbach-Horton, Megan E.; Rosario Collazo, José L.; Nicewicz, David. A. (Synlett, 2020)
Organic azides serve as synthetically useful surrogates for primary amines, a functional group which is ubiquitous in bioactive and medicinally relevant molecules. Historically, the formal hydroazidation of simple activated olefins and styrenes has proven difficult due to the inherent propensity of these compounds to oligomerize. Herein is disclosed a method for the anti-Markovnikov hydroazidation of activated olefins, catalyzed by an organic acridinium salt under irradiation from blue LEDs. This method is applicable to a variety of substituted and terminal styrenes and several vinyl ethers, yielding synthetically versatile hydroazidation products in moderate to excellent yield.
Keywords: photooxidation; alkenes; azides; radicals; regioselectivity